Agritourism and local development: Evidence from two case studies in Greece. (15th April 2018) - Karampela, Sofia; Kizos, Thanasis
Abstract: This paper attempts to fill a gap in the international literature by assessing the impacts of agritourism at local level combining different aspects. The primary data were obtained through personal in‐depth interviews with the use of semi‐structured questionnaires. Two destinations in Greece were selected due to their diverse characteristics: an island, Lesvos, and a continental locality, Plastiras Lake. Findings suggest that the differences can be summarized in structure: of agritourism supply; scale: by providing their owners with additional income in pluriactive farm households; and networks: affected by their different geographic characteristics, but are not reflected to the overall results of local development.